Persepsi Mahasiswa PGMI terhadap Relevansi Sejarah Kebudayaan Islam dalam Menanamkan Nilai-nilai Karakter Religius - Wibowo, Yusuf Rendi; Salfadilah, Fatonah; Amanabella, Maulina (ARZUSIN, 2024)
The study of Islamic Cultural History (SKI) in higher education, particularly in the PGMI program, plays a significant role in shaping students' religious character. This research aims to explore the perceptions of PGMI students on the relevance of SKI in instilling religious character values. The study used a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation of third-semester PGMI students at UIN Raden Intan Lampung. Data analysis was conducted using the Miles, Huberman, and Saldana model. The results show that students view SKI not only as a course that provides historical knowledge but also as a medium for internalizing Islamic moral and spiritual values such as honesty, patience, and discipline. Students are inspired by the exemplary behavior of Islamic figures and are motivated to apply these values in their daily lives, both in worship and social interactions. The study concludes that SKI effectively contributes to shaping students' religious character, making them more concerned with noble ethics and more disciplined in performing religious duties.